Wilderness conservation in Central Africa, from theory to practices. Looking for flexible protected areas - (:unkn) unknown (My University, 2010)
This thesis proposes an analyze of integrated wildlife conservation and development projects in Central Africa, which have been designed through community based approaches since the eighties in the framework of international projects and programs. We give an idea about conservation hotspots and protected areas' spatial representation which has became central to community based conservation initiatives. This representation is produced from a typical core/periphery contrasted relation between wild areas and production spaces. It generates stereotyped local development and governance models as well as zoning approaches shifting away from local practices and habits, particularly regarding land use and tenure issues. Consequently, this territorial centripetal representation engenders power relations and conflicts linked to protected areas management. This power games constitute obstacles to communities' active participation in the frame of conservation projects. We illustrate our analyze through a critical review of sustainable development rhetoric issues applied to wilderness management and through several applied cases studies in Central Africa. Zakouma National Park (Chad) case study and its land management experience constitute a particular example for demonstrating how conservationists use to implement their strategy in Central Africa.
Keywords: African Research